DESIGNING ACCOUNTING INFORMATION SYSTEMS TO OPTIMIZE FINANCIAL MANAGEMENT IN HANDBAG CRAFT MSMES IN BALI - Salsabila, Sisi; Putra, Yuniarti Hidayah Suyoso (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research aims to design an Accounting Information System (AIS) to optimize financial management at MSME Mozzare Shop, a woven bag craft manufacturer in Bali that has penetrated the global market. Despite success with online sales strategies during the pandemic, Mozzare Shop still relies on unstructured manual financial records, making it difficult for owners to understand financial conditions accurately. This is qualitative research with a case study approach. Data was collected through interviews, observations, and document analysis; the AIS design developed is based on the financial management system. The implementation of this AIS is expected to improve operational efficiency, recording accuracy, and transparency of Mozzare Shop's financial information, thereby supporting informed business decision-making and sustainable growth in the global market. Recommendations are proposed in this paper.